Hubungan Gaya Kepemimpinan dengan Kinerja Karyawan pada Kantor Kementerian Agama di Padang - Azzira Caesa Dija; Syamsir Syamsir; Qorry Patresia Berna; Nike Juliandari; Safri Andika (Dinasti Review Publisher, 2023)
The leadership style applied by leaders at the Ministry of Religion Office in Padang City is considered good, but employees still expect an attitude from leaders that provides a sense of security, calm, and conduciveness during work so that they are not rushed into working at the Ministry of Religion Office in Padang City. In this way, it can improve employee performance at work so that it has a positive effect on their service to the community. In this way, researchers are interested in conducting this research, to find out what strategies leaders should use regarding their leadership style to create a sense of security, comfort, and calm for employees while working. The method used in this research is a qualitative method with data collection techniques in the form of interviews and field observations at the Ministry of Religion Office in Padang City.